The impact of intimate partner violence on adverse birth outcomes in 20 sub-Saharan African countries: propensity score matching analysis - Angwach Abrham Asnake; Beminate Lemma Seifu; Alemayehu Kasu Gebrehana; Asaye Alamneh Gebeyehu; Amanuel Yosef Gebrekidan; Afework Alemu Lombebo; Amanuel Alemu Abajobir; Amanuel Alemu Abajobir (Frontiers Media S.A., 2024)
BackgroundIntimate partner violence (IPV) is a significant public health problem, with serious consequences on women's physical, mental, sexual, and reproductive health, as well as birth outcomes. Women who encounter IPV are more likely to experience adverse birth outcomes such as low birth weight, premature delivery, and stillbirth. Although numerous studies are exploring the association between IPV and adverse birth outcomes, they merely used classical models and could not control for potential confounders. The purpose of this study was to ascertain whether there was a causation between IPV and adverse birth outcomes in sub-Saharan Africa (SSA) using a quasi-experimental statistical technique [i.e., propensity score matching (PSM) analysis].MethodThis study used the most recent (2015-22) Demographic and Health Survey (DHS) data from 20 SSA countries. A total weighted sample of 13,727 women was included in this study. IPV (i.e., sexual, physical, emotional, and at least one form of IPV) was the exposure/treatment variable and adverse birth outcomes (preterm delivery, low birth weight, stillbirth, and macrosomia) were the outcome variables of this study. PSM was employed to estimate the impact of IPV on adverse birth outcomes.ResultsThe average treatment effects (ATE) of sexual, physical, emotional, and at least one form of IPV were 0.031, 0.046, 0.084, and 0.025, respectively. Sexual, physical, emotional, and at least one form of IPV increased adverse birth outcomes by 3.1%, 4.6%, 8.4%, and 2.5%, respectively. Findings from the average treatment effect on treated (ATT) showed that women who experienced sexual, physical, emotional, and at least one form of IPV had an increased risk of adverse birth outcomes by 3.6%, 3.7%, 3.3%, and 3.0%, respectively, among treated groups.ConclusionThis study demonstrates a causal relationship between IPV and adverse birth outcomes in SSA countries, indicating a need for programs and effective interventions to mitigate the impact of IPV during pregnancy to reduce related adverse pregnancy outcomes. Furthermore, we suggest further research that investigates the causal effect of IPV on adverse birth outcomes by incorporating additional proximal variables not observed in this study.